Inventing the savage: the Sapara people of the Ecuadorian Amazon in 19th-century travel writing - Rosado Valencia, Erika; Jansen, Silke; Gerique-Zipfel, Andres (Journal de la Société des américanistes, 2024)
In this article, we examine the discursive construction of the Sapara people of the Ecuadorian Amazon in the writings of travelers who explored the region in the second half of the 19th century. We focus mainly on the ways in which these writings reflect prevailing ideologies of the time, according to which “civilized” human societies could be distinguished from “savage” ones. In doing this, we analyze the representation of different aspects of the Sapara culture, such as agriculture and working habits, gender relations and sexual practices and the art of war and leisure. We frame our analysis in the theoretical proposal of Irvine and Gal for the ideological construction of cultural difference through the semiotic processes known as rhematization, fractal recursivity, and erasur
Keywords: Ecuadorian Amazon; cultural difference; 19th-century travel writing; semiotic approach; Sapara people; savagery